2013
DOI: 10.1111/j.1743-6109.2012.02984.x
|View full text |Cite
|
Sign up to set email alerts
|

Toward Personalized Sexual Medicine (Part 1): Integrating the “Dual Control Model” into Differential Drug Treatments for Hypoactive Sexual Desire Disorder and Female Sexual Arousal Disorder

Abstract: In three related manuscripts we describe our drug development program for the treatment of Hypoactive Sexual Desire Disorder (HSDD). In this first theoretical article we will defend the hypothesis that different causal mechanisms are responsible for the emergence of HSDD: low sexual desire in women (with HSDD) could be due to either a relative insensitive brain system for sexual cues or to enhanced activity of sexual inhibitory mechanisms. This distinction in etiological background was taken into account when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 103 publications
(156 reference statements)
0
36
1
Order By: Relevance
“…According to this subdivision, HSDD can be caused by low sensitivity to sexual cues or by overactivation of sexual inhibitory systems. The overinhibitors, however, possess normal sexual cue sensitivity which does not seem to be the case with the present subset [59]. Possibly, these inhibitors were underrepresented in the present subset, or the decreased GM volume may not reflect The present study could not determine whether the observed GM volume and WM FA differences cause or are caused by sexual dysfunction.…”
Section: Attentional Control and Inhibitioncontrasting
confidence: 71%
See 1 more Smart Citation
“…According to this subdivision, HSDD can be caused by low sensitivity to sexual cues or by overactivation of sexual inhibitory systems. The overinhibitors, however, possess normal sexual cue sensitivity which does not seem to be the case with the present subset [59]. Possibly, these inhibitors were underrepresented in the present subset, or the decreased GM volume may not reflect The present study could not determine whether the observed GM volume and WM FA differences cause or are caused by sexual dysfunction.…”
Section: Attentional Control and Inhibitioncontrasting
confidence: 71%
“…If sexual responses are less frequent or weaker in HSDD (e.g., because of decreased sexual cue sensitivity), self-regulation of sexual behavior (e.g., inhibiting sexual responses in inappropriate situations) may be less developed because the need for or strength of such regulation is lower. Conversely, there is also evidence that a subset of subjects with HSDD may overinhibit their sexual responses via the DLPFC [59]. According to this subdivision, HSDD can be caused by low sensitivity to sexual cues or by overactivation of sexual inhibitory systems.…”
Section: Attentional Control and Inhibitionmentioning
confidence: 99%
“…The implications of such a study would be important in elucidating the factors underlying low sexual desire—especially among women—to determine whether these women are similarly less responsive to sexual cues, that is, that they experience low state sexual desire (see Bloemers et al. [85]).…”
Section: Discussionmentioning
confidence: 99%
“…The two mechanisms are based on the idea postulated in the dual control model of sexual response [7,8] that sexual dysfunctions are caused and sustained by dysfunction in one of two separate but interacting systems, the sexual excitation and the sexual inhibition system. There is cognitive [9,10], psychophysiological [9][10][11][12][13], subjective [10][11][12], neuroanatomical [14,15] and pharmacological [9][10][11][12]15] evidence that shows that there are indeed women whose HSDD/FSIAD is caused by either a decreased propensity for sexual excitation or an increased propensity to inhibit their sexual response. The combination of testosterone and sildenafil is an ondemand (i.e.…”
Section: Introductionmentioning
confidence: 99%